European Protestantism and the Orthodox tradition of mastering the Bible: the view of the Kiev Theological Academy professors of the ХІХ – early XX centuries = Evropejskij protestantizm i pravoslavnaja tradicija usvoenija Biblii: vzgljad professorov Kievskoj duchovnoj akademii CHICH – načala CHCH v. - Golovashchenko, Sergii (Bogoslovskie razmyšlenija, 2018)
In this article the author turns to the church-historical and biblical-theological heritage of the KTA of the XIX - early XX centuries in the aspect not yet explored. For the first time, works of a number of the KTA professors have been analyzed, in which, for a long time, the experience of the Reformation and moreover, Protestant influence on the formation and development of Orthodox biblical scholarship and the tradition of public use of the Bible was comprehended. In particular, it was noted that widespread public use of the Bible since the time of the Christianization of Rus became a sign of a common Christian identity and entry into a global community of civilized peoples. Reformation influence in many ways determined the transformation of the Eastern Slavic Orthodox culture in the context of interconfessional contacts of European peoples. The tradition of Orthodox reading of the Bible, taking into account its Masoretic original, is also connected with the Protestant influence in the Kyiv-Mohyla period. And the possibility of applying the methods of biblical "high" criticism initiated the formation of scholarly Orthodox biblical studies. Finally, the world Protestant experience of applying biblical principles, norms, symbols in various spheres of social and cultural life was analyzed by Orthodox Kyiv researchers as a factor of social modernization, especially in the context of counteracting secular and revolutionary tendencies relevant at that time.